A chromosome-scale genome assembly of the grape powdery mildew pathogen Erysiphe necator reveals its genomic architecture and previously unknown features of its biology - Alex Z. Zaccaron; Tara Neill; Jacob Corcoran; Walter F. Mahaffee; Ioannis Stergiopoulos (mBio, 2023)
ABSTRACT Erysiphe necator is an obligate fungal pathogen that causes grape powdery mildew, globally the most important disease on grapevines. Previous attempts to obtain a quality genome assembly for this pathogen were hindered by its high repetitive DNA content. Here, chromatin conformation capture (Hi-C) with long-read PacBio sequencing was combined to obtain a chromosome-scale assembly and a high-quality annotation for E. necator isolate EnFRAME01. The resulting 81.1 Mb genome assembly is 98% complete and consists of 34 scaffolds, 11 of which represent complete chromosomes. All chromosomes contain large centromeric-like regions and lack synteny to the 11 chromosomes of the cereal PM pathogen Blumeria graminis. Further analysis of their composition showed that repeats and transposable elements (TEs) occupy 62.7% of their content. TEs were almost evenly interspersed outside centromeric and telomeric regions and massively overlapped with regions of annotated genes, suggesting that they could have a significant functional impact. Abundant gene duplicates were observed as well, particularly in genes encoding candidate secreted effector proteins. Moreover, younger in age gene duplicates exhibited more relaxed selection pressure and were more likely to be located physically close in the genome than older duplicates. A total of 122 genes with copy number variations among six isolates of E. necator were also identified and were enriched in genes that were duplicated in EnFRAME01, indicating they may reflect an adaptive variation. Taken together, our study illuminates higher-order genomic architectural features of E. necator and provides a valuable resource for studying genomic structural variations in this pathogen. IMPORTANCE Grape powdery mildew caused by the ascomycete fungus Erysiphe necator is economically the most important and recurrent disease in vineyards across the world. The obligate biotrophic nature of E. necator hinders the use of typical genetic methods to elucidate its pathogenicity and adaptation to adverse conditions, and thus comparative genomics has been a major method to study its genome biology. However, the current reference genome of E. necator isolate C-strain is highly fragmented with many non-coding regions left unassembled. This incompleteness prohibits in-depth comparative genomic analyses and the study of genomic structural variations (SVs) that are known to affect several aspects of microbial life, including fitness, virulence, and host adaptation. By obtaining a chromosome-scale genome assembly and a high-quality gene annotation for E. necator, we reveal the organization of its chromosomal content, unearth previously unknown features of its biology, and provide a reference for studying genomic SVs in this pathogen.